Aktivisme Twitter: crowdsourcing melalui tagar #100jutamaskerchallenge - Zulfi I. Putraji (Jurnal Komunikasi Profesional, 2022)
The development of internet technology has become an important part in social and political movements. Social media is an important channel for the digital activism movement in the information era. This study examines the hashtag (#) in driving digital opinion and how hashtags act as a crowdsourcing platform, the method used is virtual ethnography by collecting tweet data related to the hashtag #100JutaMaskerChallenge. The concept of digital activisim and crowdsourcing used to analyze this digital phenomenon. The results of the study shows hashtags as an important factorfor digital activists in gathering information and trigger a movement in the real world.